Career choices for anaesthesia: national surveys of graduates of 1974-2002 from UK medical schools. - Turner, G; Goldacre, M; Lambert, T; Sear, J (2005)
BACKGROUND: Knowledge about UK doctors' career intentions and pathways is essential for understanding future workforce requirements. The aim of this study was to report career choices for and career progression in anaesthesia in the UK. METHODS: Postal questionnaire surveys were undertaken of qualifiers from all UK medical schools in nine qualification years since 1974. RESULTS: 74% (24623/33417) and 73% (20709/28468) of doctors responded at 1 and 3 yr after qualification. At 1 and 3 yr after qualification, on average, 8% of doctors chose anaesthesia. Between 1974 and 2002 the percentage of doctors choosing anaesthesia, 1 yr after qualification, increased from 5 to 12%. A majority of doctors who chose anaesthesia 1 and 3 yr after qualification were working in anaesthesia 10 yr after qualification. In addition to doctors' enthusiasm for the specialty, career choices for anaesthesia were positively influenced by their perception of working hours, conditions of work, and career and promotion prospects. CONCLUSIONS: Anaesthesia has become increasingly popular as a career choice in the UK. Training numbers could be increased in the short term to speed up the process of providing a consultant-delivered service.